2013
DOI: 10.1007/s00701-013-1853-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute brain reaction to DBS electrodes after deep brain stimulation: chronological observation

Abstract: We report here our chronological observations of acute brain reactions after DBS procedures, which we believe are neither infectious nor vascular, but are possibly caused by the mechanical breakdown of the blood-brain barrier by microelectrode recordings or by anchored DBS electrodes. These lesions are thought to constitute a self-limiting disorder requiring no further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
0
32
1
Order By: Relevance
“…The approximate incidence of this finding was of 0.4% and thus the authors defined it as a rare complication. In past years other authors have described radiological findings consistent with peri-electrode edema in patients following DBS lead placement [2][3][4][5][6][7][8][9][10][11][12][13]. The literature indicates an extremely wide range from 0.4% [10] to 39% [2] for this complication.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The approximate incidence of this finding was of 0.4% and thus the authors defined it as a rare complication. In past years other authors have described radiological findings consistent with peri-electrode edema in patients following DBS lead placement [2][3][4][5][6][7][8][9][10][11][12][13]. The literature indicates an extremely wide range from 0.4% [10] to 39% [2] for this complication.…”
Section: Discussionmentioning
confidence: 92%
“…In past years other authors have described radiological findings consistent with peri‐electrode edema in patients following DBS lead placement . The literature indicates an extremely wide range from 0.4% to 39% for this complication.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These investigators suggested that the cause of cyst formation was tracked CSF during placement of the DBS lead or, alternatively, because of an autoimmune or inflammatory response to the DBS hardware. 4,5 Acute brain parenchymal reaction resulting from lead insertion has been suggested as a mechanism for rare findings of low-attenuation signal around the DBS lead after surgery by Kim et al 6 They described 7 cases of transient increased lowattenuation signals that circumferentially surrounded DBS electrodes. The signal extended into the subcortical white matter and was associated with unexpected and transient neurological symptoms during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%